2007
DOI: 10.1111/j.1469-8749.2007.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Bruininks–Oseretsky Test of Motor Proficiency for identifying children with motor impairment

Abstract: This study compared the consistency of the Short Form (SF) and the Long Form (LF) of the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP) in identifying preschool children with motor impairment (MI). One hundred and forty-four Greek preschool children participated (74 males, 70 females; mean age 5y 2mo [SD 5mo], range 4y 6mo-5y 6mo). Although total SF and LF scores were highly correlated (r=0.85), paired t-tests indicated significant differences (t=-27.466, p=0.001). SF total scores (mean 58.72 [SD 7.28]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 13 publications
6
41
3
6
Order By: Relevance
“…Descriptive statistics showed that 25% of the tested children had "low motor proficiency," 57% had "average motor proficiency," and 18% had "high motor proficiency". The percentage of children with low motor proficiency in the current study is slightly above that of BOTMP standardization sample (23%; Bruininks, 1978), but well below the percentage (35%) found in the study of Venetsanou et al (2007) in which Greek children of the age of 5 participated. At this point, it should be noted that the above categorization of children's performance must be interpreted with caution, because the suitability of the original BOTMP norms for Greek population has yet to be examined.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Descriptive statistics showed that 25% of the tested children had "low motor proficiency," 57% had "average motor proficiency," and 18% had "high motor proficiency". The percentage of children with low motor proficiency in the current study is slightly above that of BOTMP standardization sample (23%; Bruininks, 1978), but well below the percentage (35%) found in the study of Venetsanou et al (2007) in which Greek children of the age of 5 participated. At this point, it should be noted that the above categorization of children's performance must be interpreted with caution, because the suitability of the original BOTMP norms for Greek population has yet to be examined.…”
Section: Discussioncontrasting
confidence: 82%
“…Moreover, Cronbach's alpha was found to be .89. Finally, both the BOTMP-LF and its balance subtest have been used in several studies conducted in Greece (Proviadaki, 2004;Venetsanou & Kambas, 2011;Venetsanou, Kambas, Aggeloussis, Serbezis, & Taxildaris, 2007). A child's performance on the BOTMP-LF can be scored in various ways.…”
Section: Methodsmentioning
confidence: 99%
“…When adding to the present results the findings of our previous study 1 according to which BOTMP-SF does not appear to constitute a valid test for 2 the identification of MI in 5-year-old children (Venetsanou et al, 2007), it is 3 concluded that the suitability of the aforementioned battery for preschool age 4 is questionable. 5…”
Section: Discussionmentioning
confidence: 42%
“…Our research confirms the results of McEvoy and Grimmer [25], who found that in children aged 5-12, there is no relationship between gender and the extent of angular movement when standing. On the other hand, there are studies showing that sexual dimorphism affects the process of controlling body posture mainly during puberty [6,13,19,22,26,28,38].…”
Section: Discussionmentioning
confidence: 99%